Penerapan Penetapan Jaza`ul Ihsan Pada Kontrak Pembiayaan Al-Qardhul Hasan Perspektif Ekonomi Islam - Tri Puspita Sari, Rina; Muhajir, Muhajir (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
The journal entitled "The Application of Determination of Jaza'ul Ihsan on Al-Qardhul Hasan Financing Contracts with an Islamic Economic Perspective" is motivated by a draft contact in the application of financing for al-qardhul hasan products in several Islamic Financial Institutions, especially in KSPPS BMT NU in East Java which includes: contains the request for a jaza'ul ihsan fee (reciprocity) which is set at the beginning of the contract when the customer wants a loan with the product, so that at the time of repayment, the customer using the al-qardhul hasan product is required to pay off the loan fee according to the loan nominal and added with jaza'ul ihsan in accordance with the agreement in the contract. This study aims to analyze the application of the determination of jaza'ul ihsan to al-qardhul hasan financing contracts associated with several explanations, rules and opinions of experts on Islamic Economics in the hope of being a problem solving of every contract issue, especially in al-qarhul hasan financing products. The methodology or approach used in this paper uses a library research method or approach, while data collection is carried out by reviewing several books, journal and documents (both printed or electronic) as well as from several types of information or data sources that have been collected. relevant to the study. The results of this study conclude that the determination of jaza'ul ihsan on the al-qardhul hasan financing contract is contrary to the aims and objectives of al-qardhul hasan in Islamic Economics because the term al-qardhul hasan is not in fiqh muamalah but the rules are equated with will qard (debt). ) both in the provisions and rules described in the Qur'an, hadith or opinions of madhhabs and Islamic economists. Keywords: Jaza'ul ihsan, al-qardhul hasan product, financing contract, Islamic Economics